Oriental Design / Ummi Kalthsum Abd Sani ... [et al.] - Abd Sani, Ummi Kalthsum; Ibrahim, Husna; Mohd Hashim, Siti Farah Suraya; Abu Mansor, Siti Sara; Shamsuddin, Wan Shazwani (Faculty of Office Management & Technology, 2005)
Administration is one aspect that important to a business. It is because administrations will manage about human problems such as workers and human is the biggest factors. If there are no labor or workers, we are sure that our Service cannot be produced effectively. Administrations Department according to our Company, will manage all administration aspects such as salaries, allowances, our financial flow, our budget, admin task, personnel matters, workers* medical Claims and holidays, Office equipment and it also require our responsibilities of Human Resources Management.